2022
DOI: 10.21203/rs.3.rs-1847006/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does the feedback of blood results in observational studies influence response and consent? A randomised study of the Understanding Society Innovation Panel

Abstract: Background: While medical studies generally provide health feedback to participants, in observational studies this is not always the case due to logistical and financial difficulties, or concerns about changing observed behaviours. However, evidence suggests that lack of feedback may deter participants from providing biological samples. This paper investigates the effect of offering feedback of blood results on participation in biomeasure sample collection.Methods: Participants aged 16 and over from a longitud… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 5 publications
(14 reference statements)
0
16
0
Order By: Relevance
“…The dotted line represents the point of no difference between the 2 groups, and the dashed line represents the average effect of all studies when pooled together. Data for 10 longitudinal studies [49][50][51][52][53][54][55][56][57] of patients 18-96 years old were obtained solely from a single study by Thompson et al, 48 including GS, which refers to the Generation Scotland−the Scottish Family Health Study; TwinsUK, the UK adult Twin Registry; and USOC, the Understanding Society−the UK Household Longitudinal Survey. OR indicates odds ratio.…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
“…The dotted line represents the point of no difference between the 2 groups, and the dashed line represents the average effect of all studies when pooled together. Data for 10 longitudinal studies [49][50][51][52][53][54][55][56][57] of patients 18-96 years old were obtained solely from a single study by Thompson et al, 48 including GS, which refers to the Generation Scotland−the Scottish Family Health Study; TwinsUK, the UK adult Twin Registry; and USOC, the Understanding Society−the UK Household Longitudinal Survey. OR indicates odds ratio.…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
“…In this sense, it differs from many COVID-19 surveys, as it used a probability sample generated by a major household panel study. The representativeness of the data has been evaluated frequently; the high-quality data allow population inferences ( Benzeval et al, 2020 ; Fisher et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…School closures might have placed additional burdens on single parents as they might have more competing responsibilities in and outside the home. Using the Understanding Society COVID-19 data, Benzeval et al (2020) found single parents faced more economic loss than others during the lockdown. Single parents might also have been less able to dedicate time and resources to home school their children.…”
Section: Family Background and Educational Inequalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Data is collected at both the household and individual level, with the household level design enabling the inclusion of information about the partner's employment status. Understanding Society is generally representative of British society (Benzeval et al, 2020), with the sample's educational and ethnic distribution mirroring that of the 2011 census.…”
Section: Datamentioning
confidence: 99%